2020
DOI: 10.1101/2020.04.11.037358
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Low tolerance for transcriptional variation at cohesin genes is accompanied by functional links to disease-relevant pathways

Abstract: Variants in DNA regulatory elements can alter the regulation of distant genes through spatialregulatory connections. In humans, these spatial-regulatory connections are largely set during early development, when the cohesin complex plays an essential role in genome organisation and cell division. A full complement of the cohesin complex and its regulators is important for normal development, since heterozygous mutations in genes encoding these components are often sufficient to produce a disease phenotype. The… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…20 For example, genes associated with trans-acting eQTLs are enriched for loss of function intolerance. 21 Thus, a better way to annotate non-coding variants to impacted genes, protein levels, and pathways is to investigate their enrichment in control elements and assign functions via methods which attribute these variants to gene regulation. [22][23][24] One approach to achieve this is to integrate information on the 3-dimensional arrangement of DNA into the functional analyses.…”
Section: Introductionmentioning
confidence: 99%
“…20 For example, genes associated with trans-acting eQTLs are enriched for loss of function intolerance. 21 Thus, a better way to annotate non-coding variants to impacted genes, protein levels, and pathways is to investigate their enrichment in control elements and assign functions via methods which attribute these variants to gene regulation. [22][23][24] One approach to achieve this is to integrate information on the 3-dimensional arrangement of DNA into the functional analyses.…”
Section: Introductionmentioning
confidence: 99%
“…However, the GTEx catalogue lists thousands of genetic variants in healthy individuals that are associated with local control of RAD21 expression (cis-eQTLs) 20 . Our previous work found that many of these variants in cis-eQTLs are also associated with co-regulation of a network of genes involved in complex disease processes 21 . Our results indicated spatial eQTLs as identifying disease associations through mechanisms alternative to those disease associations found via GWAS.…”
Section: Introductionmentioning
confidence: 99%